Practical aspects of modern model family education in Ukraine - Milash, O. (Problems of Engineer-Pedagogical Education, 2018)
The essence of the process of education, which is regarded as a purposeful, organized the formation of the individual qualities of the individual, stable views of the surrounding reality and life in society, moral ideals, norms and attitudes, habits, etc. It is proved that the basic education of every person in the family receives. It is shown that the modern Ukrainian family has a number of problems, many of which are associated with a mismatch child-rearing practices as a legal and moral requirements. It was determined that the most common mistakes parents is a misconception about the features of manifestation of parental feelings; lack of knowledge of parents about child development and age-appropriate methods of educational influence it; underestimation of the role of personal example of parents, and the unity of the requirements for a child. It stressed the need for the organization of special education for the parents to raise the level of psychological and pedagogical knowledge and practical skills in the sphere of interaction with their children at all stages of their personal development. It is alleged that this training should be based on the implementation of learnercentric model of family education.